Exosomal non-coding RNAs: orchestrators of intercellular crosstalk in the prostate cancer tumor microenvironment - Duan, Huanglin; Xu, Baisheng; Luo, Peiyue; Chen, Tao; Zou, Jun (Frontiers in Immunology, 2025)
Prostate cancer (PCa) remains a leading cause of cancer-related mortality in men worldwide, primarily due to its propensity for therapy resistance and metastasis. Emerging evidence underscores that exosomes, nanoscale extracellular vesicles, act as critical mediators of intercellular communication within the tumor microenvironment (TME), particularly via the non-coding RNAs (ncRNAs) they transport. These molecules include microRNAs (miRNAs), circular RNAs (circRNAs), and long non-coding RNAs (lncRNAs). Exosomal ncRNAs drive tumor progression, immune evasion, and therapy resistance by reprogramming neighboring stromal cells, immune cells, and malignant cells. This review systematically examines the multifaceted roles of exosomal ncRNAs in remodeling the prostate cancer tumor microenvironment, focusing on their communication between tumor cells, tumor-stromal cells (including immune cells), and within the pre-metastatic niche preceding bone metastasis. We emphasize their mechanisms of action and clinical relevance. These findings position exosomal ncRNAs as central drivers of prostate cancer progression, revealing novel diagnostic and therapeutic opportunities. Future research must address challenges in standardizing exosome isolation techniques, resolving spatiotemporal heterogeneity, and advancing clinical translation to fully realize the potential of exosome-based strategies in precision oncology.